2005
DOI: 10.1213/01.ane.0000147519.82841.5e
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic Management and One-Year Mortality After Noncardiac Surgery

Abstract: Little is known about the effect of anesthetic management on long-term outcomes. We designed a prospective observational study of adult patients undergoing major noncardiac surgery with general anesthesia to determine if mortality in the first year after surgery is associated with demographic, preoperative clinical, surgical, or intraoperative variables. One-year mortality was 5.5% in all patients (n = 1064) and 10.3% in patients > or =65 yr old (n=243). Multivariate Cox Proportional Hazards modeling identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
445
2
31

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 819 publications
(494 citation statements)
references
References 31 publications
16
445
2
31
Order By: Relevance
“…Corroborating earlier work, 87 this study also found a substantial relationship between POCD and death within 1 year of surgery. 88,89 Independent risk factors for sustained POCD included greater age, less education, POCD at hospital discharge, and a history of stroke without residual damage.…”
Section: Postoperative Cognitive Dysfunction After Noncardiac Surgerysupporting
confidence: 90%
See 1 more Smart Citation
“…Corroborating earlier work, 87 this study also found a substantial relationship between POCD and death within 1 year of surgery. 88,89 Independent risk factors for sustained POCD included greater age, less education, POCD at hospital discharge, and a history of stroke without residual damage.…”
Section: Postoperative Cognitive Dysfunction After Noncardiac Surgerysupporting
confidence: 90%
“…118 In a separate group of rats, they found that the same nitrous oxide exposure profoundly, but transiently, reduced the activity of cortical methionine synthase-an enzyme that is implicated in dementia and may be related to accumulation of homocysteine (a cytotoxic amino acid normally remethylated to methionine, an essential amino acid, by methionine synthase). 118 Evidence from Monk's 2005 study indicated that cumulative deep hypnotic time is associated with more POCD, 87 with a substantial relationship between POCD and death within 1 year of surgery. 88,89 In distinction, a study by Schubert's group looked at lighter anesthesia (bispectral index [BIS] 50) versus deeper anesthesia (BIS 39) and found that deeper levels of anesthesia were associated with better cognitive function 4-6 weeks postoperatively.…”
Section: Aggravating Factorsmentioning
confidence: 99%
“…These results were confirmed in another group of patients assigned by baseline TP. It has been demonstrated that hypotension during anaesthesia may worsen patient outcome [23][24][25]. More than 50 years ago, Kleinerman et al [23] showed that the degree of hypotension correlated with the decrease of cerebral blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…A MAP decrease of 26% resulted in a decrease of cerebral blood flow of 12%, whereas a MAP decrease of 50% correlated with a drop of cerebral blood flow of 20%. Monk et al identified three independent risk factors for 1-year mortality following surgery in 1064 patients, one of which was intra-operative hypotension [24]. A third investigation found that the incidence of postoperative delirium was higher (9% vs 4%) in patients with MAP between 45 and 55 mmHg compared with patients with MAP between 55 and 70 mmHg [25].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with the results reported by Monk et al, who found that the mortality rate during the first postoperative year might be affected by anesthetic management. 22 In an observational study of 1,064 patients, they found that the Charlson comorbidity index score, cumulative deep hypnotic time, and intraoperative hypotension (systolic blood pressure \ 80 mmHg) were significant independent predictors of the one-year mortality rate. Brown et al also found that the hypnotic depth might be associated with the one-year mortality rate in elderly patients during repair of hip fractures under spinal anesthesia.…”
Section: Discussionmentioning
confidence: 99%